Overweight and obese women’s symptoms, knowledge, and preferences regarding endometrial biopsy for endometrial cancer detection: A threshold technique survey - Anna L. Beavis; Zishan Hirani; Tullia Rushton; Mary Catherine Rush; Amanda N. Fader; Gayane Yenokyan; Anne F. Rositch (Gynecologic Oncology Reports, 2024)
Background: The incidence of endometrial cancer (EC) in the United States continues to rise, driven mainly by the obesity epidemic. We sought to determine overweight and obese women’s cancer risk knowledge and preferences regarding diagnostic endometrial biopsy (EMB) for EC detection. Methods: An online survey was administered to overweight and obese women without EC recruited through the electronic medical record’s online patient portal. Baseline questions queried gynecologic history, cancer risk knowledge, and factors potentially influencing decision-making for EMB. We used the threshold survey technique to identify the minimum acceptable risk (MAR) threshold at which each respondent would be willing to undergo an EMB to detect EC. Results: Of 357 respondents (median age 45 years (interquartile range [IQR]: 38–54); median BMI 39 [IQR: 36.0–44.6]), fewer than half (48.7 %) were aware that obesity is a risk factor for EC, and 10 % considered their risk of EC to be high. Almost half (42 %) of respondents reported MAR thresholds characterized as very low (0–1 %), and these were more common among respondents with higher BMIs. Forty percent identified their weight as a factor influencing their MAR threshold decision, while 76 % identified their perceived personal risk as a factor. Less than half cited immediate risks of the procedure. Conclusion: Many patients reported being willing to undergo an EMB at very low risk thresholds for EC. Perceived personal risk is a stronger factor in decision-making than immediate procedural risks. Providers should focus on communicating patients’ risk to motivate EMB to detect EC where appropriate.